The Challenges of Islamic Fintech Growth in Indonesia: A Bibliometric Analysis - M. Nur Ikhwan; Awaludin Taufiq; Aditya Darmawan; Inna Khoridatul Bahiya; Ikin (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2026)
Objective: The aim of this study is to explore the dynamics and difficulties associated with Islamic fintech by integrating the emerging themes from the existing literature. Design/Methods/Approach: Using bibliometric analysis and VOSviewer, the research examines 686 publications from the CrossRef database (2018-2024) through keyword co-occurrence networks, overlay visualization, and density analysis. Findings: The intellectual structure reveals a dense collaboration network centered on core actors, with B. Koderi and Basyar Syaripudin as the most active nodes, while Gunarto A emerges as the most productive author. The co-word structure indicates that Islamic fintech scholarship is organized around a problem-solving logic with